2009
DOI: 10.1093/cercor/bhp212
|View full text |Cite
|
Sign up to set email alerts
|

Role of Late Maternal Thyroid Hormones in Cerebral Cortex Development: An Experimental Model for Human Prematurity

Abstract: Hypothyroxinemia affects 35–50% of neonates born prematurely (12% of births) and increases their risk of suffering neurodevelopmental alterations. We have developed an animal model to study the role of maternal thyroid hormones (THs) at the end of gestation on offspring's cerebral maturation. Pregnant rats were surgically thyroidectomized at embryonic day (E) 16 and infused with calcitonin and parathormone (late maternal hypothyroidism [LMH] rats). After birth, pups were nursed by normal rats. Pups born to LMH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 68 publications
2
59
0
Order By: Relevance
“…This concurs with our finding that CH had thinning in the superior frontal gyrus and thickening in the middle frontal sulcus. Current findings are also consistent findings of local migration abnormalities in sensorimotor, auditory, and visuospatial cortices of TH-deprived rodents (11,23).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This concurs with our finding that CH had thinning in the superior frontal gyrus and thickening in the middle frontal sulcus. Current findings are also consistent findings of local migration abnormalities in sensorimotor, auditory, and visuospatial cortices of TH-deprived rodents (11,23).…”
Section: Discussionsupporting
confidence: 88%
“…In other words, cortical thickening may represent a more juvenile pattern of brain development than seen in TDC. Additionally, some neurons failing to reach the cortical plate may have remained in lower layers or even the white matter, thus giving the appearance of an abnormally long-and hence thicker-cortex (11). Also, these migrational failures could lead to heterotopias, as observed in autism (25), which coincidentally is also associated with gestational TH insufficiency (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 These studies have shown changes in cerebellum with reductions in weight and cell number, and delayed maturation. The influence of maternal hypothyroxinemia on neocortical development has been recently studied in rats and mice.…”
Section: Hypothyroxinemia and Neurodevelopmentmentioning
confidence: 99%
“…Further, it is essential for the proper development and function of the Central Nervous System. 2 Since the first epidemiological studies conducted by Pharoah 3 and Thilly 4 in the 70's, the association between iodine deficiency in pregnant women and fetal neurological damage has been extensively reviewed and proven in scientific literature. In fact, the need to provide iodine supplementation to pregnant women in iodine-deficient regions is considered as proven by scientific evidence.…”
Section: Introductionmentioning
confidence: 99%